Sensitivity Analysis Techniques Applied in Video Streaming Service on Eucalyptus Cloud Environments. Issue 1 (2018) - Melo, Rosangela; Bezerra, Maria Clara; Dantas, Jamilson; Matos, Rubens
No abstract available